Coerced Confessions and the Fourth Amendment - Mannheimer, Michael J. Zydney (2002)
Coerced confessions in State criminal prosecutions have been thought to implicate the Due Process Clause of the Fourteenth Amendment, as well as the Self-Incrimination Clause of the Fifth Amendment. However, pursuant to Graham v. Connor, if an interest is addressed by one of the specific clauses of the Bill of Rights that has been incorporated against the States, only the standards associated with that provision- and not the more generalized notions of Due Process- apply to a claim that the interest has been infringed. Accordingly, one might think that the law of coerced confessions is governed entirely by the Self- Incrimination Clause. However, by its very terms, the Self-Incrimination Clause forbids a State only from forcing a person to be a witness against himself in a criminal case. Thus, the Clause is violated, if ever, only in a formal judicial proceeding, and the victim of police torture whose statements are never used against him would have no constitutional redress. In this Article, Mr. Mannheimer argues that the coerced confession should be viewed primarily as a Fourth Amendment event: it is the product of an unreasonable continuing seizure of the suspect, and, in addition, the product of an unreasonable search of his or her mind. Mr. Mannheimer further argues that, in order to determine whether a confession was coerced, courts should utilize a Fourth Amendment reasonableness analysis, which departs in some significant ways from current law